2014
DOI: 10.1002/path.4482
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1 accelerates tumourigenesis by regulating the WNT signalling pathway

Abstract: We investigated the oncogenic role of SETDB1 focusing on non-small cell lung cancer (NSCLC) having high expression of this protein. A total of 387 lung cancer cases were examined by immunohistochemistry, 72% of NSCLC samples were positive for SETDB1 staining, compared to 46% samples of normal bronchial epithelium (106 cases) (p<0.0001). Percent positive cells and intensity of staining increased significantly with increased grade of disease. Forced expression of SETDB1 in NSCLC cell lines enhanced their clonoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 52 publications
9
85
1
Order By: Relevance
“…Alternatively, ATF7IP could simply act as a safety mechanism to prevent SETDB1 overactivity. Amplification of SETDB1 is heavily implicated in tumorigenesis (Ceol et al., 2011, Fei et al., 2015, Rodriguez-Paredes et al., 2014, Sun et al., 2014, Sun et al., 2015, Wong et al., 2016), and upregulation of ATF7IP has been observed in a number of tumors (Liu et al., 2009), suggesting that overexpression of SETDB1 could have deleterious effects. Given that no effective small molecule inhibitors of SETDB1 catalytic activity have been developed, our data raise the possibility that an alternative strategy to inhibit SETDB1 activity could be to target ATF7IP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, ATF7IP could simply act as a safety mechanism to prevent SETDB1 overactivity. Amplification of SETDB1 is heavily implicated in tumorigenesis (Ceol et al., 2011, Fei et al., 2015, Rodriguez-Paredes et al., 2014, Sun et al., 2014, Sun et al., 2015, Wong et al., 2016), and upregulation of ATF7IP has been observed in a number of tumors (Liu et al., 2009), suggesting that overexpression of SETDB1 could have deleterious effects. Given that no effective small molecule inhibitors of SETDB1 catalytic activity have been developed, our data raise the possibility that an alternative strategy to inhibit SETDB1 activity could be to target ATF7IP.…”
Section: Discussionmentioning
confidence: 99%
“…However, four additional methyltransferases (G9a, GLP, SUV39H1, and SUV39H2) are also known to target H3K9, raising the question as to how the activities of these enzymes are coordinately regulated to generate the required distribution of H3K9 methylation across the genome (Mozzetta et al., 2015). The importance of correct regulation of SETDB1 is underscored by the oncogenic potential of SETDB1 overexpression, with amplification of SETDB1 implicated in the progression of malignant melanoma (Ceol et al., 2011) and cancers of the prostate (Sun et al., 2014), liver (Fei et al., 2015, Wong et al., 2016), and lung (Rodriguez-Paredes et al., 2014, Sun et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…A study has demonstrated the role of histone lysine methyltransferases SUV39H1 and SETDB1 in gliomagenesis and its association with cell proliferation, migration, and colony formation (43). Another study found that SETDB1 positively stimulated the WNT/β-catenin pathway and decreased P53 expression, resulting in enhanced non-small cell lung cancer growth in vitro and in vivo (44). Some authors have shown that miR-7, which is downregulated in the breast cancer MCF-7 and MDA-MB-231 cell lines, inhibited cell invasion and metastasis, decreased the breast cancer stem cell population, and partially reversed the epithelial-mesenchymal transition in MDA-MB-231 cells by directly targeting SETDB1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…The data from the GeneCards database show that the SETDB1 protein is involved in three classical pathways: chromatin regulation/acetylation, non-canonical Wnt signaling, and lysine degradation. A number of studies suggest that SETDB1 promotes tumorigenesis and metastasis through the WNT/β-catenin pathway (44,47). However, further studies are required to assess this point.…”
Section: Discussionmentioning
confidence: 99%
“…Amplifications of SETDB1 have been reported in 20% of lung adenocarcinoma and squamous cell carcinoma, and funcional studies suggest a contribution to tumorigenesis, possibly through modulatin of the wnt pathway (Rodriguez-Paredes et al, 2014;Wu et al, 2014;Sun et al, 2015). Furthermore, SETDB1 is likely the critical gene in the recurrent large amplification of chromosome 1q21 in melanoma (Ceol et al, 2011).…”
Section: Modulation Of Global and Locus-specific H3k9 Methylation By mentioning
confidence: 94%